1996
DOI: 10.1037/0735-7044.110.6.1205
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of place learning in children as measured in the Radial Arm Maze, Morris Search Task, and Open Field Task.

Abstract: Children and adults were tested on 3 place learning tasks. Children under the age of 7 were inferior to older subjects in solving the tasks by using spatial relational solutions, but subjects of all ages were equally proficient in solving the task by using simple stimulus-reward associations (cued solutions). Accurate performance on the cued versions suggests that neither the general response demands nor the large size of testing environments rendered the tasks differentially inappropriate for young children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
162
3
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 70 publications
(110 reference statements)
20
162
3
2
Order By: Relevance
“…Even though we have previously shown that adults need no verbal instructions to understand the goal of our task and to exhibit successful performance ), a pilot study had shown that older children (48-60 months) were very uncomfortable not receiving any kind of verbal instruction or feedback, and were in fact performing worse than younger children (30-45 months) who seemed to have no problem understanding the goal of the task (i.e., find rewards at fixed spatial locations). Interestingly, Overman and colleagues found very similar results in a Morris search task (Overman et al, 1996). When not given information about the static nature of the goal location, 4-year-olds performed worse than 3-year-olds.…”
Section: Testing Proceduressupporting
confidence: 58%
See 4 more Smart Citations
“…Even though we have previously shown that adults need no verbal instructions to understand the goal of our task and to exhibit successful performance ), a pilot study had shown that older children (48-60 months) were very uncomfortable not receiving any kind of verbal instruction or feedback, and were in fact performing worse than younger children (30-45 months) who seemed to have no problem understanding the goal of the task (i.e., find rewards at fixed spatial locations). Interestingly, Overman and colleagues found very similar results in a Morris search task (Overman et al, 1996). When not given information about the static nature of the goal location, 4-year-olds performed worse than 3-year-olds.…”
Section: Testing Proceduressupporting
confidence: 58%
“…The majority of other studies have restricted their investigations of allocentric spatial capacities to children three years and older, and these studies have repeatedly shown that (1) the performance of 3-year-olds on allocentric spatial tasks is inferior to that of older children; (2) children show marked improvement in their allocentric capacities between four and six years of age; and (3) for most of the tasks employed, children's performance becomes adult-like sometime between seven and ten years of age (Bullens et al, 2010;Foreman et al, 1984Foreman et al, , 1990Lehnung et al, 1998;Leplow et al, 2003;Mandolesi, Petrosini, Menghini, Addona, & Vicari, 2009;Nardini, Burgess, Breckenridge, & Atkinson, 2006;Overman et al, 1996;Pentland, Anderson, Dye, & Wood, 2003;Smith et al, 2008). Thus, with the possible exception of Newcombe's study (Newcombe et al, 1998), no study has unequivocally demonstrated that children under three years of age are capable of solving a task which requires the use of an allocentric spatial representation, a fundamental component of episodic memory.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations